(untitled) (HEALTH CARE: JURNAL KESEHATAN, 2024)
Background: Bullying behavior is very vulnerable to occurring when individuals are teenagers because they are entering the process of finding their identity in the environment. There are several factors that cause bullying behavior, one of the factors that causes bullying behavior is wrong parenting patterns. Parenting patterns are a child’s description of the attitudes and behavior of parents and children in interaction and communication during parenting. Objective: to determine the relationship between parenting patterns and bullying behavior in adolescents. Method: This research is quantitative with a cross sectional design. The population in this research is all students in class VIII of junior high school with a sample size of 96 respondents. Data was collected and then statistical data processing was carried out by SPSS. Results: Obtained p-value = 0.000 (≤ 0.05) which means there is a significant relationship between parenting patterns and adolescent bullying behavior. Conclusion:. There is a significant relationship between parental parenting patterns and adolescent bullying behavior.